2022
DOI: 10.1002/jsfa.11783
|View full text |Cite
|
Sign up to set email alerts
|

The drip loss inhibitory mechanism of nanowarming in jumbo squid (Dosidicus gigas) mantles: protein structure and molecular dynamics simulation

Abstract: BACKGROUND The magnetic nanoparticles plus microwave thawing (MNPMT), a new rewarming technology entitled ‘nanowarming’, can serve as an effective method to achieve rapid and uniform thawing, thus reducing drip loss. The purpose of this study was to decipher the drip loss inhibitory mechanism of MNPMT in jumbo squid (Dosidicus gigas) from the perspectives of protein structure and ice crystal recrystallization. A number of different techniques such as dynamic rheology, Raman spectra, intrinsic fluorescence meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…MFI is an index of protein degradation and meat tenderness [ 51 ]. It has been reported that the higher the MFI value, the worse the integrity of the internal structure of myofibrils [ 52 ]. In our study, the MFI showed that the totality of myofibrils and proteins clearly deteriorated with age, the spaces between myofibrils getting larger, and thus leading to severe fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…MFI is an index of protein degradation and meat tenderness [ 51 ]. It has been reported that the higher the MFI value, the worse the integrity of the internal structure of myofibrils [ 52 ]. In our study, the MFI showed that the totality of myofibrils and proteins clearly deteriorated with age, the spaces between myofibrils getting larger, and thus leading to severe fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…The above results can be attributed to the cross‐linking of the myosin head and denaturation of rod sub‐fragments or light meromyosin (Jiang & Xiong, 2013). Subsequently, the sharply decreased G ′ at 45−70°C is probably due to actomyosin denaturation/cross‐linking caused by oxidation (Li et al., 2022c). These changes reduce the viscoelasticity of the proteins and damage their network structures to varying degrees (Cai et al., 2018).…”
Section: Thawing‐induced Mp Denaturationmentioning
confidence: 99%
“…The precipitate dissolved in four volumes of Tris-HCl-NaCl solution (20 mmol/L). Afterward, the compound was homogenized at 6000 rpm for 30 s and centrifuged at 6500× g for 15 min, and the supernatant was MP [17].…”
Section: Determination Of Protein and Lipid Oxidation 271 Myofibrilla...mentioning
confidence: 99%